Meningococcal serogroup B disease in Turkey A guess or reality? - (:unkn) unknown (TAYLOR & FRANCIS INC, 2014)
Each country chooses the appropriate vaccine against IMD depending on the locally prevalent serogroups of N. meningitides. Frequency of each meningococcal serogroup varies considerably over time and by geographical location. Despite the majority of IMD cases (85%) are caused by serogroups B and C in Europe, true prevalence of serogroup B IMD cases in Turkey is unclear. In one of the recent studies, the sharp decrease of serogroup B IMD from 35% down to 2.5% in a few years despite the absence of vaccination is confusing. Millions of European Turkish people travels from Europe to Turkey every year who could most probably carry serogroup B. It is obvious that a nationwide active surveillance is crucial to assess the the true epidemiology and burden of IMD which has a major impact on the choice of vaccine type and age interval the vaccination to be implemented.
Keywords: invasive; meningococcal; diseases; epidemiology; serogroup B; Turkey; surveillance; vaccine; BACTERIAL-MENINGITIS; EPIDEMIOLOGY